Pemanfaatan Game Edukasi untuk Meningkatkan Kemampuan Literasi Peserta Didik SD N 2 Ponjen - Yunita, Ika Romadoni; Hikma Rosalia, Shafni Nur; Utriani, Tiya (Universitas Pahlawan Tuanku Tambusai, 2024)
Reading literacy skills are really needed by students along with the rapid development of information and technology. Improving elementary school students' literacy is very important because literacy is a basic skill needed to succeed in education and everyday life. The literacy problem of elementary school students in Purbalingga is caused by various factors, including students who are less motivated to read and write, so they face difficulties in improving their literacy skills, in addition to being caused by a lack of interest in the available reading materials. Educational games (Educational Games) can be an effective tool for improving elementary school students' literacy skills. Educational games can provide various benefits in developing literacy skills. The solution that will be implemented to solve partner problems is carrying out learning activities by utilizing educational games (Educational Games) to improve the literacy skills of students at SD Negeri 2 Ponjen. As a result of this activity, participants had high enthusiasm, apart from that it had increased literacy through educational games. This activity succeeded in increasing participants' interest in reading and writing skills